Ni-Mn bimetallic oxide nanosheets as high-performance electrode materials for asymmetric supercapacitors. (October 2019) - Tang, Xiaohui; Zhang, Bowei; Lui, Yu Hui; Hu, Shan
Graphical abstract: Highlights: Ni-Mn bimetallic oxide shows a maximum specific capacitance of 574 F/g at 1A/g. The specific capacitance can be retained as high as 472 F/g at 32A/g. An asymmetric supercapacitor with the voltage window of 2.1 V is fabricated. A high energy density of 27 Wh/kg was attained. 82.3% of its initial capacitance can be reached after 8000-cycle GCD test at 4A/g. Abstract: Using bimetallic oxide as the electrode material of supercapacitor is emerging as a promising approach to supply better pseudocapacitive performance than that from the electrodes made of corresponding single metal oxides. Herein, Ni-Mn bimetallic oxide nanosheets (Ni-MnBMO) on carbon cloth substrate were synthesized through a facile hydrothermal method. With the help of cyclic voltammetry activation process, the prepared A-Ni-MnBMO electrode exhibits the maximum specific capacitance 574 F g −1 (within a potential range of −0.2–1.2 V vs. Ag/AgCl at 1 A g −1 after excluding the effects of OER) mainly due to the reversible redox reactions of Mn 3+ /Mn 4+ . Moreover, to prove its potential as the positive electrode in a supercapacitor, an asymmetric supercapacitor with a voltage range of 2.1 V is fabricated by using functional carbon nanotube as the negative electrode and 1 M Na2 SO4 as the electrolyte. As a result, the device can deliver a maximum energy density of 27 Wh kg −1 (at 0.5 A g −1 ) and 82.3% of its initial specific capacitance can be maintained after 8000 cycles of galvanostatic charge and discharge tests at 4 A g −1 .